Lifetime violence and suicidal ideation among young women (18–24 years) in Uganda: Results from a population-based survey - Kisaakye, Peter; Kafuko, Agatha; Bukuluki, Paul (Frontiers in Global Women's Health, 2023)
Introduction Violence is a major global public health issue that threatens the physical and mental health of victims. Of particular concern is the increasing evidence which suggests that violence is strongly associated with suicidal behavior including ideation. Methods This study uses data from the 2015 Violence Against Children Survey (VACS). This study seeks to highlight the relationship between lifetime violence and suicidal ideation using a nationally representative sample of 1,795 young women (18–24 years) in Uganda. Results Results indicate that respondents who experienced lifetime sexual violence (aOR = 1.726; 95%CI = 1.304–2.287), physical violence (aOR = 1.930; 95%CI = 1.293–2.882) or emotional violence (aOR = 2.623; 95%CI = 1.988–3.459) were more likely to experience suicidal ideation. Respondents who were not married (aOR = 1.607; 95%CI = 1.040–2.484), not having too much trust with community members (aOR = 1.542; 95%CI = 1.024–2.320) or not having a close relationship with biological parents (aOR = 1.614; 95%CI = 1.230–2.119) were more likely to experience suicidal ideation. Respondents who did not engage in work in the past 12 months prior to the survey (aOR = 0.629; 95%CI = 0.433–0.913) were less likely to experience suicidal ideation. Conclusion The results can be used to inform policy and programming and for integration of mental health and psychosocial support in programming for prevention and response to violence against young women.